*Answer :*

(Here the third factor can be further factorised as shown)

*x*

= (x

= (x + y)(x – y)(x^{6}– y^{6}= (x^{2})^{3}– (y^{2})^{3}= (x

^{2}– y^{2})[(x^{2})^{2}+ x^{2}y^{2}+(y^{2})^{2}]= (x + y)(x – y)(x

^{4}+ x^{2}y^{2}+ y^{4})(Here the third factor can be further factorised as shown)

*= (x + y)(x – y)(x*

= (x + y)(x – y)[(x

= (x + y)(x – y) (x^{4}+ 2x^{2}y^{2}+ y^{4}– x^{2}y^{2})= (x + y)(x – y)[(x

^{2}+ y^{2})^{2}– x^{2}y^{2}]= (x + y)(x – y) (x

^{2}+ y^{2}+ xy)(x^{2}+ y^{2}– xy)*Rate this question :*

*How useful is this solution?*

We strive to provide quality solutions. Please rate us to serve you better.

*Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses*

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation